Plasmodium falciparum: Genetic diversity and complexity of infections in an isolated village in western Thailand - Kazuyuki Tanabe (2018)
© 2013 Elsevier Ireland Ltd.. Genetic diversity of Plasmodium falciparum is intimately associated with morbidity, mortality and malaria control strategies. It is therefore imperative to study genetic makeup and population structure of this parasite in endemic areas. In Kong Mong Tha, an isolated village in western Thailand, the majority of P. falciparum infections are asymptomatic. In this study we investigated complexity of infections and single nucleotide polymorphisms (SNPs) in the P. falciparum population of Kong Mong Tha, and compared results with those previously obtained from Mae Sod, in northwestern Thailand, where the majority of infections were symptomatic. Using PCR-based determination of the 5' merozoite surface protein 1 gene (msp1) recombinant types, we found that 39% of 59 P. falciparum isolates from Kong Mong Tha had multiple 5' recombinant types with a mean number of 1.54. These values were much lower than those obtained from Mae Sod: 96% for multiple infections and with a mean number of 3.61. Analysis of full-length sequences of two housekeeping genes, the P-type Ca2+-transporting ATPase gene (n=33) plus adenylosuccinate lyase gene (n=33), and three vaccine candidate antigen genes, msp1 (n=26), the circumsporozoite protein gene, csp (n=30) and the apical membrane antigen 1 gene, ama 1 (n=32), revealed that in all of these genes within-population SNP diversity was at similar levels between Kong Mong Tha and Mae Sod, suggesting that the extent of MOI and clinical manifestations of malaria are not strongly associated with genetic diversity. Additionally, we did not detect significant genetic differentiation between the two parasite populations, as estimated by the Wright's fixation index of inter-population variance in allele frequencies, suggesting that gene flow prevented the formation of population structuring. Thus, this study highlights unique features of P. falciparum populations in Thailand. The implications of these finding are discussed.